Symptomatic joint hypermobility is not a barrier to attendance, graduation, or satisfaction for adults participating in a multidisciplinary pain rehabilitation program - Flegge, Lindsay G.; Estrella, Emma; Harris, Elizabeth K.; Hirsh, Adam T.; Bushey, Michael A. (Frontiers in Pain Research, 2025)
IntroductionSymptomatic joint hypermobility, as found in conditions like hypermobile Ehlers-Danlos syndrome (hEDS), presents unique challenges in pain management due to associated symptoms such as chronic pain, joint instability, and dysautonomia. Despite the high prevalence of hypermobility and associated healthcare costs, there is a lack of research on effective treatments for these patients, particularly in the context of multidisciplinary pain rehabilitation programs.ObjectiveThis study aims to compare the baseline characteristics, attendance, graduation rates, and patient satisfaction of hypermobile and non-hypermobile adult outpatients participating in a multidisciplinary pain rehabilitation program (PRP).MethodsThis retrospective cohort study analyzed clinical data from 335 patients at the Indiana University Health Pain Navigation Service between January 1, 2023, and December 31, 2023. Baseline characteristics were assessed using patient-reported outcome measures, and attendance and graduation rates were tracked. Hypermobile and non-hypermobile groups were compared with independent samples t-tests and chi-squared tests. A multiple linear regression model was used to assess the impact of hypermobility diagnosis on PRP attendance, with pertinent demographic and baseline clinical scores entered as covariates.ResultsHypermobile patients differed significantly from non-hypermobile patients in demographics, including age, gender, race, education, and employment status. Despite these differences, hypermobile patients did not differ from non-hypermobile patients in PRP attendance or graduation rates. Baseline pain, depression, and pain catastrophizing scores were lower in the hypermobile group. Exit surveys indicated similar levels of overall satisfaction with the program, though hypermobile patients were less likely to report that their needs were fully met than were non-hypermobile patients.DiscussionDespite the potential for joint hypermobility to pose a barrier to participation in multidisciplinary pain rehabilitation programs, we found no evidence that patients with a hypermobile diagnosis had less participation in an intensive outpatient pain rehabilitation program. After accounting for group differences in key demographic and clinical variables, there were no significant differences in PRP attendance between hypermobile and non-hypermobile patients. Our results are encouraging regarding the potential for multidisciplinary pain rehabilitation programs to serve the needs of these patients.